สัณฐานและองค์ประกอบธาตุของฝุ่นละอองที่มีขนาดเล็กกว่า 10 ไมครอน ในกรุงเทพมหานคร - ศิริวรรณ แก้วงาม (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The particulate matters in some areas of Bangkok exceeded the average standard concentration and the road site is higher than ambient site. PM10 (24 hr.) concentration in the rainy is 65.60 microgram/qb.m. and 97.65 microgram/qb.m. in the winter. The ratio of PM10 to TSP is more than 50%. The average concentration of organic carbon (OC) in PM10 in the rainy is 31.21 microgram/qb.m. and the winter is 26.49 microgram/qb.m. Their morphology and element composition are studied in order to identify their emission source. Particulates from diesel fuel are flocculent association and porous flufly with loose structure through carbon, oxygen and sulfur as the main composition. Their dimensions are about 7-10 micron. Particles from the benzene fuel are fluffy aggregation, porous and sponge like. The main compositions are carbon, oxygen, sulfur, their average size is about 4-5 micron. The particles from combustion are rigid crust as square shape with mainly calcium composition. The average size is among 8-10 micron. Particles from a power plant are soft plate, smooth with multiple layers. They consist of carbon, oxygen and sulfur with dimension are about 10 micron. The soil particles are hard irregular block shape with bigger size about 10 micron and silica, calcium and aluminum are the main composition. The main particlate in Bangkok is from diesel-benzene fuel particle and the minor is from construction